Palmitoleic Acid Decreases Non-alcoholic Hepatic Steatosis and Increases Lipogenesis and Fatty Acid Oxidation in Adipose Tissue From Obese Mice - Cruz, Maysa M.; Simão, Jussara J.; Sá, Roberta D. C. C. de; Farias, Talita S. M.; Silva, Viviane S. da; Abdala, Fernanda; Antraco, Vitor J.; Armelin-Correa, Lucia; Alonso-Vale, Maria Isabel C. (Frontiers in Endocrinology, 2020)
We recently demonstrated that palmitoleic acid (C16:1n7), a monounsaturated FA, increases the metabolic and oxidative capacity of 3T3-L1 adipocytes. Herein, the effect of 16:1n7 supplementation on metabolic parameters on white adipose tissue (WAT) and liver of obese mice induced by a high-fat diet (HFD) was addressed by analyzing metabolic (dys) function and altered genes expression in adipose tissue, as well liver and serum biochemistry analysis. For this purpose, mice were induced to obesity for 8 weeks, and from the 5th week, they received 16:1n7 (300 mg/kg/day) or water for 30 days, by gavage. Subcutaneous inguinal (ING) and epididimal (EPI) WAT were removed for analysis of metabolic, (anti) inflammatory, adipogenic and thermogenic genes expression by real-time RT-PCR. Additionally, metabolic activities of isolated adipocytes, such as glucose uptake, lipogenesis (triacylglycerol esterification), -oxidation and lipolysis in ING adipocytes were also assessed. Despite the higher fat intake, the HFD group showed lower food intake but higher body weight, increased glucose, significant dyslipidemia, and increased liver and adipose depots mass, accompanied by liver steatosis. The 16:1n7 supplementation slowed down the body mass gain and prevented the increase of lipids in the liver. HFD+n7 animals presented increased fatty acid oxidation and lipogenesis compared to Control, but no effect was observed on lipolysis and glucose uptake in ING isolated adipocytes. Besides, 16:1n7 increased the content of the mRNA encoding FABP4, but partially prevented the expression of genes encoding ATGL, HSL, Perilipin, Lipin, C/EBP-α, PPAR-γ, C/EBP-β, CPT1, NRF1, TFAM, PRDM16 and NOS2 in ING depot from HFD group of animals. Finally, HFD increased Mcp1 and Tnfα expression, and 16:1n7 promoted a more marked increase in it. In summary, the data show that palmitoleic acid promotes metabolic changes and partially prevents the increase in gene expression on adipocytes triggered by obesity, suggesting that HFD+n7 animals do not require the same magnitude of metabolic adaptation to cope with energy demand from the HFD. In the long term, the effects of 16:1n7 may be more evident and beneficial for the function/dysfunction of WAT from an obese organism, with relevant repercussions in the systemic metabolic homeostasis.